Strategic Budget Realization Analysis for Evaluating Financial Performance at the Liukang Kalmas Sub-district Office, Pangkep Regency - Suarni, Agusdiwana; Nasrullah, Nasrullah; Rahmah, Miftahul (Universitas Muhammadiyah Makassar, 2025)
Study This aiming For know performance finance government area Office Sub-district Head Liukang Kalmas District . The Pangkep inrange year 2019-2023 via observation to ratio finance that is ratio efficiency and ratio effectiveness . Method analysis Which used that is analysis descriptive quantitative through observation to ratio finance ratio efficiency, and ratio effectiveness . Data collection techniques are with Field Research Technique ( Research) Field ) which is collection data with do observation And analysis to reporting realization Sub-district Office Budget (LRA) Liukang Kalmas , Pangkep Regency. Research results This show that percentage from performance Sub-district Office Finance Liukang Kalmas District . The Pangkep with ratio efficiency performance finance Sub-district Office Liukang Kalmas, Pangkep Regency is at a lower level efficient, where the level of efficiency obtained for 5 years in a row everything is at in the range of 90%-100%. And to ratio effectiveness Sub-district Office Performance Liukang Kalmas, Pangkep Regency Already including Good Where percentage its effectiveness still is at 100% and above every the year, so that interpreted that the percentage has been very effective.